Identification of a Novel Quinvirus in the Family Betaflexiviridae That Infects Winter Wheat - Kondo, Hideki; Yoshida, Naoto; Fujita, Miki; Maruyama, Kazuyuki; Hyodo, Kiwamu; Hisano, Hiroshi; Tamada, Tetsuo; Andika, Ida Bagus; Suzuki, Nobuhiro (Frontiers in Microbiology, 2021)
Yellow mosaic disease in winter wheat is usually attributed to the infection by bymoviruses or furoviruses; however, there is still limited information on whether other viral agents are also associated with this disease. To investigate the wheat viromes associated with yellow mosaic disease, we carried out de novo RNA-seq analyses of symptomatic and asymptomatic wheat-leaf samples obtained from a field in Hokkaido, Japan, in 2018 and 2019. The analyses revealed the infection by a novel betaflexivirus which tentatively named wheat virus Q (WVQ), together with wheat yellow mosaic virus (WYMV, a bymovirus) and northern cereal mosaic virus (a cytorhabdovirus). BLAST analyses showed that the WVQ strains (of which there are at least three) were related to the members of the genus Foveavirus in the subfamily Quinvirinae (family Betaflexiviridae). In the phylogenetic tree, they form a clade distant from that of the foveaviruses, suggesting that WVQ is a member of a novel genus in the Quinvirinae. Laboratory tests confirmed that WVQ, like WYMV, is potentially transmitted through the soil to wheat plants. WVQ was also found to infect rye plants grown in the same field. Moreover, WVQ-derived small interfering RNAs accumulated in the infected wheat plants, indicating that WVQ infection induces antiviral RNA silencing responses. Given its common coexistence with WYMV, the impact of WVQ infection on yellow mosaic disease in the field warrants detailed investigation.